Quasi-Isothermal External Short Circuit Tests Applied to Lithium-Ion Cells: Part II. Modeling and Simulation. Issue 2 (1st January 2019) - Rheinfeld, Alexander; Sturm, Johannes; Noel, Andreas; Wilhelm, Jörn; Kriston, Akos; Pfrang, Andreas; Jossen, Andreas
Abstract : Measurement data gained from quasi-isothermal external short circuit tests on single-layered pouch-type Li-ion cells presented in the first part of this combined work was used to validate a well-known homogenized physical-chemical model for different electrode loadings, cell temperatures, initial cell voltages, and external short circuit resistances. Accounting for diffusion-limited reaction kinetics, effective solid phase diffusion coefficients, and one representative active material particle size within each electrode, the model is capable of describing the experimentally observed characteristic change in magnitudes of current and heat generation rate throughout the short circuit. Underlying mechanisms for the observed characteristics are studied by evaluating the predicted concentration distribution across the electrodes and separator and by calculating the cell polarization due to ohmic losses, diffusion processes, and reaction kinetics. The importance of mass transport in the solid and liquid phase limiting reaction kinetics is discussed and evaluated in the context of a sensitivity analysis. Concentration dependent transport properties, electrode tortuosity, particle size, and electrode energy density are affecting different stages of a short circuit. Simulation results suggest a strong impact of electrode design on the short circuit dynamics allowing for an optimization regarding a cell's energy and power characteristics whilst guaranteeing a high short circuit tolerance.